Lessons Learned from an Obstetrics/Newborn/Neonatal Intensive Care Full-Scale Exercise. Issue Volume 34:Issue s1(2019) (May 2019) - Cooper, Arthur; Frogel, Michael; Foltin, George
Abstract : Introduction: Children are frequently victims of disasters. However, gaps remain in disaster planning for pediatric patients. The New York City Pediatric Disaster Coalition (NYCPDC) is funded by the New York City Department of Health and Mental Hygiene (DOHMH) to prepare NYC for mass casualty incidents that involve large numbers of children. Aim: On April 26, 2018, the NYCPDC conducted a first full-scale exercise with the New York Fire Department (FDNY) testing evacuation, patient tracking, communications, and emergency response of the obstetrics, newborn, and neonatal units at Staten Island University Hospital North. The goal of the exercise was to evaluate current obstetrics/newborn/neonatal plans and assess the hospital's ability to evacuate patients. Methods: The exercise planning process included a review of existing obstetrics/newborn/neonatal plans, four group planning meetings, specific area meetings, and plan revisions. The exercise incorporated scenario-driven, operations-based activities, which challenged participants to employ the facility's existing evacuation plans during an emergency. Results: The exercise assessed the following: communication, emergency operation plans, evacuation, patient tracking, supplies, and staffing. Internal and external evaluators rated exercise performance on a scale of 1-4. Evaluators completed an exercise evaluation guide based on the Master Scenario Event List. An After Action Report was written based on the information from the exercise evaluation guides, participant feedback forms, hot wash session, and after-action review meeting. Strengths included the meaningful improvement of plans before the exercise (including the fire department) and the overall meeting of exercise objectives. Discussion: Lessons learned included: addressing gaps in effective internal and external communications, adequate supplies of space, staff, and equipment needed for vertical evacuations in addition to providing staging and alternate care sites with sufficient patient care and electrical power resources. The lessons learned are being utilized to improve existing hospital plans to prepare for future full-scale exercise and or real-time events.